The EFL Undergraduate Students and English Reading Styles: Evidence from One English Education Program - Fortunasari Fortunasari; Rd. M. Ali; Lili Lestari; Harlina Harja; Siti Rahma Sari; Sri Hidayati (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2022)
The study was aimed to investigate the students’ English reading learning styles used by EFL undergraduate students. The participants were students from one English study program at Faculty Teacher Training and Education in Jambi, which aims to produce teachers in English teaching. This study used total sampling with 75 participants consisting of 22 participants in the second semester, and 53 participants in the sixth semester. The analysis of the data was based on the students’ response to twenty five statements that consist of five parts: there are auditory, kinesthetic, group, visual, and individual. For which they were required to choose any of five alternatives namely strongly agree, agree, not sure, disagree, and strongly disagree. The results revealed that the most preferred reading learning style among the respondents was the auditory learning style and the least is visual learning style. Then, for the gender male used kinesthetic learning style and female used auditory learning style. In this study, suggestions for future research, students, lectures and university are also discussed.